Understanding the community interest of breast cancer in Indonesia: a digital epidemiology study using Google trends - Atina Husnayain; Anis Fuad (Berita Kedokteran Masyarakat (BKM), 2018)
Introduction. Breast cancer was count for 30.5% of all cancers diagnosed in Indonesia. Although preventable, breast cancer is mostly diagnosed in advanced stages and caused leading dead among females. Given the increasing growth of online information seeking behavior, adequate cancer health promotion through virtual setting is needed to tackle the massive increasing burden of breast cancer. Therefore this study aims to explore the community interest in breast cancer using Google Trends. Method. 5 years (from September 2013 to August 2018) information searches for breast cancer from Google were retrieved in Indonesian language. Data were downloaded at national and sub-region level to examine the pattern and distribution of queries. Results. Sporadic traces of information searches related to breast cancer from Google Trends presented the pattern and distribution of queries. Massive search happened in July 2015 and June 2017 following the died of Indonesian celebrity who suffered from breast cancer. However, the cancer awareness month every October does not impact the number of information searches. Considering the high influence of celebrities, many studies reveal the positive impact of celebrities involvement in health promotion. Celebrity can attract the public attention to health messages and increase the agreement of vaccination and screening for cancer. Thereby, celebrities involvement and availability of qualified breast cancer online information should be increased to win the breast cancer health promotion program in the digital era. Online information related to breast cancer could be disseminated through targetted risk population using Mobile JKN that has been downloaded by 1.5 million members. Conclusion. Google Trends could be potentially used as a novel tool to measure the dynamics of community interest in breast cancer in Indonesia. Therefore, adequate cancer health promotion through a virtual setting is the key to tackling the massive increasing burden of breast cancer in the digital era.